The Legal Status of Non-Muslim Heirs in Islamic Inheritance Law: A Comparative Study of Indonesia, Malaysia, and Egypt from the Perspective of al-Maqasid al-Shari’ah - Setiani, Siti Afria Dwi; Rouf, Abd. (Tebuireng: Journal of Islamic Studies and Society, 2026)
This research is motivated by the differences in the regulation of the legal status of non-Muslim heirs in Islamic inheritance law across various Muslim countries, which continue to leave unresolved issues of justice within pluralistic societies. The main issue lies in the provisions of classical Islamic jurisprudence (fiqh), which regard differences in religion as an impediment to inheritance. However, in contemporary practice, various alternative mechanisms, such as wasiat wajibah (mandatory bequest), have emerged to address the need for justice in interfaith families. This study aims to analyze the legal status of non-Muslim heirs in Islamic inheritance law in Indonesia, Malaysia, and Egypt from the perspectives of maqāṣid al-syarī‘ah and justice. The method employed is normative legal research using a comparative legal approach and a conceptual approach based on maqāṣid al-syarī‘ah. The results of the study indicate that Indonesia accommodates non-Muslim heirs through the jurisprudence of wasiat wajibah, Malaysia maintains a conservative approach by rejecting interfaith inheritance and relying on hibah (inter vivos gifts), while Egypt has institutionalized wasiat wajibah through formal regulations. These differences reflect a shift from formal justice toward substantive justice in contemporary Islamic inheritance law.